Study of collective action for cheese differentiation in the province of Trento, Italian Alps. An institutional approach - Carine Pachoud (Revue de Géographie Alpine)
Collective action for quality differentiation of food products linked to a territory is a long-term process. It is often hindered by a lack of understanding of multilevel institutional dynamics. This article aims at conducting a socio-historical analysis of the institutional context allowing the development of a specific cheese value-chain in the province of Trento (Italian Alps). Using Ostrom’s institutionalist approach, we conducted a historical analysis of the formal and informal multilevel institutions. Our results showed that a subsistence economy prevailed between 1800 and 1950, which implied little commitment from the producers to build up collective organisations, despite government and church incentives. When the “modernisation” of agriculture started around 1950, it meant that the production could be intended for the market, which enabled the development of producers’ cooperatives. The province became autonomous in 1948 and supported those local dynamics. Since then, we have observed an increasing level of trust among the different local actors and towards the provincial government. Since 2000, the valorisation of cheese specificity has become a central strategy to face competition at different levels. However, at the same time the production has undergone intensification. This leads to a loss of the link between product and territory. The future challenge is therefore to implement innovative institutional arrangements that allow a sustainable differentiation of cheese.